Durable complete response to immunotherapy with anti‐PD‐1 antibody nivolumab in a patient with oral squamous cell carcinoma presenting with lung metastasis: A case report. Issue 9 (30th August 2021) - Sekido, Katsuhisa; Imaue, Shuichi; Tomihara, Kei; Tachinami, Hidetake; Yamagishi, Kentaro; Okazawa, Seisuke; Ikeda, Atsushi; Fujiwara, Kumiko; Noguchi, Makoto
Abstract: Although the optimal treatment method for metastatic oral cancer remains largely unknown, the present case suggests that immunotherapy is a potentially promising alternative for metastatic oral cancer in which other therapies are no longer effective. Abstract : Although the optimal treatment method for metastatic oral cancer remains largely unknown, the present case suggests that immunotherapy is a potentially promising alternative for metastatic oral cancer in which other therapies are no longer effective.